PENGARUH STRES KERJA, KEPUASAN KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA PERAWAT (Studi pada RS Panti Wilasa Citarum Semarang) - Difayoga, Rama; Yuniawan, Ahyar (Faculty of Economics and Business Diponegoro University, 2015)
For improve boarding costs sunset employees, organizations and charged forÂ hobby consider factors - factors that can influence such as job stress , job satisfaction and work environment. In this case the organization's hospital and or and institutions engaged in service Medical Service then immersed boarding costs and optimal employee both can improve boarding costs hospital sets the hearts achieve its vision and mission.This study aimed to analyze the effect of job stress, job satisfaction, and work environment on the performance of nurses. This study was conducted at Hospital Nursing Wilasa Citarum Semarang. The number of samples specified by 67 respondents using simple random sampling method and measurement questionnaire with Likert scale . Data analysis method used is multiple linear regression analysis using SPSS program as aid.Against the hypothesis testing results, showing that the negative effect of work stress variables sunset Nurses Against boarding costs. Job satisfaction has positive effect Against the immersed Nurse boarding costs. Against a positive work environment influence the setting Nurse boarding costs. The coefficient of determination total sum of 50.3 % indicates that the ability of independent variables ( job stress, job satisfaction, and work environment ) hearts explain the dependent variable ( boarding costs sunset Nurse ) very limited. From the findings of Multiple Linear Regression Analysis that influence job satisfaction Hobby big boarding costs sunset Against Nurses.